Penyusunan Bibliogrrafi Beranotasi Karya Mohammad Hatta di Perpustakaan Proklamator Bung Hatta Bukittinggi - Ilham, Muhammad; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
This article aims to describe the manufacture of bibliography annoted by Mohammad Hatta in the Library ofÂ  Proclamator Bung Hatta Bukittinggi. The method used is descriptive with engineering data collection through direct observation. Observation is done by collecting and recorded collections of libraries to the subject of Muhammad Hatta in the Library of Ploclamator Bung Hatta Bukittinggi. After the data obtained through, next to identify on the parts that will be made to bibliography annotated. Based on the discussion, it can be concluded in the manufacture of bibliography annotated at the Library of Proclamator Bung Hatta Bukittinggi is as follow. First, the determination of the title by look at (a) the availability of library collections to the subject of Mohammad Hatta, (b) using collection of Mohammad Hatta, and (c) the information in the collection are still well preserved. Second, the library with records of authors, the title, and impresum. Third, the selection of library which aims to cut between the title of bibliography with the library collected. The four, grouping or classification. The five, prepation the keyword. And than, typing a bibliography.Keyword: bibliography, Bung Hatta, library.